2009
DOI: 10.1063/1.3147863
|View full text |Cite
|
Sign up to set email alerts
|

Structures generated in a temperature filament due to drift-wave convection

Abstract: A simplified numerical study is made of the structures that are formed in a magnetized temperature filament due to oscillatory convection from large amplitude drift waves. This study is motivated by a recent experiment ͓D. C. Pace, M. Shi, J. E. Maggs et al., Phys. Plasmas 15, 122304 ͑2008͔͒ in which Lorentzian-shaped temporal pulses are observed. These pulses produce a broadband, exponential frequency power spectrum. The model consists of an electron heat transport equation in which plasma convection arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Because, in TJ-K, it has been previously established that drift-wave turbulence is a dominant factor, it can be further concluded that drift-waves play a key role in the generation of the pulses. Such a concept has been shown to explain 36 the Lorentzian pulses observed in the temperature gradient experiments in LAPD. However, it should be emphasized that, at the present time, there is no analytic calculation or modeling that directly explains why the temporal shape for density fluctuations observed in TJ-K should be Lorentzian.…”
Section: Discussionmentioning
confidence: 84%
“…Because, in TJ-K, it has been previously established that drift-wave turbulence is a dominant factor, it can be further concluded that drift-waves play a key role in the generation of the pulses. Such a concept has been shown to explain 36 the Lorentzian pulses observed in the temperature gradient experiments in LAPD. However, it should be emphasized that, at the present time, there is no analytic calculation or modeling that directly explains why the temporal shape for density fluctuations observed in TJ-K should be Lorentzian.…”
Section: Discussionmentioning
confidence: 84%
“…The threshold corresponds to the ExB velocity imparted by the modes exceeding the phase velocity of the modes (approximately the diamagnetic drift velocity). The experimental observations [16][17][18] and the model results [19] also show that the value of the parameter τ is a fraction (1/4 to 1/5) of the wave period of the drift-modes.…”
mentioning
confidence: 94%
“…The underlying chaos is associated with coherent drift-waves driven unstable by the pressure gradients. A modeling study [19] has shown that retaining two individual modes is sufficient to result in the generation of Lorentzian pulses when the amplitude of the modes exceeds a threshold value. The threshold corresponds to the ExB velocity imparted by the modes exceeding the phase velocity of the modes (approximately the diamagnetic drift velocity).…”
mentioning
confidence: 99%
“…The methodology used to describe classical transport in the hollow-ring system follows the successful approach developed earlier 3,6,7,10 for the small-filament experiments. But suitable changes are made to model the different boundary conditions associated with the LaB 6 ring source, notably the plasma collection property of the cathode structure and the related axial-flow velocity.…”
Section: Classical Transportmentioning
confidence: 99%
“…Over the past fifteen years, a series of basic electron heat transport experiments [1][2][3][4][5][6][7] have been performed in the Large Plasma Device (LAPD) 8 operated by the Basic Plasma Science Facility (BaPSF) at the University of California, Los Angeles (UCLA). From detailed comparisons of the observations with theoretical and numerical modeling studies, [9][10][11][12] new insights were obtained that led to the identification that density fluctuations in tokamaks are chaotic. 13 The workhorse for those earlier experiments was a small (3 mm diameter), single-crystal LaB 6 emitter that injected a low-voltage electron beam into a strongly magnetized (1 kG), cold, afterglow-plasma.…”
Section: Introductionmentioning
confidence: 99%